Plasma centrifugation does not influence thrombin-antithrombin and plasmin-antiplasmin levels but determines platelet microparticles count - Stępień, Ewa (Biochem Med (Zagreb), 2015)
INTRODUCTION: Centrifugation is an essential step for plasma preparation to remove residual elements in plasma, especially platelets and platelet-derived microparticles (PMPs). Our working hypothesis was that centrifugation as a preanalytical step may influence some coagulation parameters. MATERIALS AND METHODS: Healthy young men were recruited (N = 17). For centrifugation, two protocols were applied: (A) the first centrifugation at 2500 x g for 15 min and (B) at 2500 x g for 20 min at room temperature with a light brake. In protocol (A), the second centrifugation was carried out at 2500 x g for 15 min, whereas in protocol (B), the second centrifugation involved a 10 min spin at 13,000 x g. Thrombin-antithrombin (TAT) and plasmin-antiplasmin (PAP) complexes concentrations were determined by enzyme-linked immunosorbent assays. PMPs were stained with CD41 antibody and annexin V, and analyzed by flow cytometry method. Procoagulant activity was assayed by the Calibrated Automated Thrombogram method as a slope of thrombin formation (CAT velocity). RESULTS: Median TAT and PAP concentrations did not differ between the centrifugation protocols. The high speed centrifugation reduced the median (IQR) PMP count in plasma from 1291 (841-1975) to 573 (391-1010) PMP/µL (P = 0.001), and CAT velocity from 2.01 (1.31-2.88) to 0.97 (0.82-1.73) nM/min (P = 0.049). Spearman’s rank correlation analysis showed correlation between TAT and PMPs in the protocol A plasma which was (rho = 0.52, P < 0.050) and between PMPs and CAT for protocol A (rho = 0.74, P < 0.050) and protocol B (rho = 0.78, P < 0.050). CONCLUSION: Centrifugation protocols do not influence the markers of plasminogen (PAP) and thrombin (TAT) generation but they do affect the PMP count and procoagulant activity.